2000
DOI: 10.1002/1521-3765(20001002)6:19<3600::aid-chem3600>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Properties of Phthalocyanine–Fullerene Hybrids

Abstract: Phthalocyanines linked to C60 have been synthesized by two general strategies. One of them involves the addition of an azomethine ylide prepared in situ from a formyl phthalocyanine to C60, and the other one involves a statistical condensation of two substituted phthalonitriles, one of them bearing the C60 moiety covalently attached. These new phthalocyanine-fullerene dyads have been studied by cyclic voltammetry and Osteryoung square wave voltammetry, and inter- and intramolecular electronic interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 39 publications
2
87
0
Order By: Relevance
“…Salome Rodreguez Morgade Gouloumis et al [42] reported the synthesis of benzoxazole derivatives. The aza-Wittig reaction of the triphenyl phosphoranylideneamino-1,4-benzoquinone with aryl isocyanates and aryl chlorides allows the preparation of benzoxazole derivatives (72).…”
Section: Jyothi and Merugumentioning
confidence: 99%
“…Salome Rodreguez Morgade Gouloumis et al [42] reported the synthesis of benzoxazole derivatives. The aza-Wittig reaction of the triphenyl phosphoranylideneamino-1,4-benzoquinone with aryl isocyanates and aryl chlorides allows the preparation of benzoxazole derivatives (72).…”
Section: Jyothi and Merugumentioning
confidence: 99%
“…In particular, as shown in the laboratories of Torres, van Lier, and many others, the mono-iodo A 3 B phthalocyanines 62 can easily be made to undergo a variety of coupling reactions (Scheme 23). 218,220,221,223,227,228,[236][237][238][239][240][241][242] This precursor can be used for the introduction of direct carboncarbon bonds as aryl, alkenyl, and alkynyl substituents. 217,219,220,226,234,235 In addition, the Buchwald reaction can be used for carbon-nitrogen bond formation.…”
Section: Cross-coupling Approachmentioning
confidence: 99%
“…218,220 Similarly, palladium-catalyzed Stille reaction between monoiodo-substituted A 3 B phthalocyanines 62 and tributylstannylethylene leads to formation of the vinyl-containing phthalocyanine 74 (Scheme 26). 221 In another synthetic strategy, carboxaldehyde-containing asymmetric phthalocyanine could be used for preparation of alkene-substituted phthalocyanines. The aldehydic A 3 B phthalocyanines can be prepared in two steps.…”
Section: Scheme 25mentioning
confidence: 99%
See 2 more Smart Citations